Axial Spondyloarthropathies in the Western Cape - Smith, Robert (Department of Medicine, 2020)
Impaired Health-Related Quality of Life and Work Productivity amongst South African patients with Axial Spondyloarthritis. Background: No studies have investigated health-related quality of life (HRQoL) or work productivity in patients with axial spondyloarthritides (axSpA) living in sub-Saharan Africa. Methods: This cross-sectional study of adults with axSpA collated demographic particulars and patient questionnaires: Bath Ankylosing Spondylitis Disease Activity Index (BASDAI); Bath Ankylosing Spondylitis Functional Index (BASFI); Bath Ankylosing Spondylitis Global Score (BASG); Medical Short Form (SF)-36; and Work Productivity and Activity Impairment Questionnaire: Specific Health Problem (WPAI:SHP). Results: Of 36 patients, the mean (SD) age was 40.3 (13.3) years and mean (SD) diagnostic delay was 8.7 (8.4) years. Most patients were male (80.6%) and of mixed racial ancestry (69.4%). Most (66.7%) patients were smokers and only 5 (13.9%) patients received tumor necrosis factor inhibitor (TNFi) therapy. The mean (SD) BASDAI was 5.3 (2.1), and 72.2% had a BASDAI ≥ 4. Patients with a high BASDAI (i.e. BASDAI ≥ 4) had higher BASG scores (p=0.003), higher WPAI:SHP activity impairment scores (p=0.003), and poorer SF-36 scores, particularly in the role-physical, bodily pain, and social functioning domains (p=0.0001, 0.001 and 0.02 respectively). Activity impairment according to the WPAI:SPH was 57.4%, with the BASDAI and activity impairment correlating closely (p=0.006). The SF-36 scores were low in physical (particularly role-physical, bodily pain, and general health) and mental (notably vitality and role emotional) domains. 6 Conclusion: This study describes a cohort of South African patients with axSpA who have poor prognostic features including diagnostic delay and cigarette smoking. Active disease, impaired function, poor physical- and mental HRQoL, and work disability are unmet needs.